A Prediction of NPVR ≥ 80% of Ultrasound-Guided High-Intensity Focused Ultrasound Ablation for Uterine Fibroids - Yang, Mei-Jie; Yu, Ren-Qiang; Chen, Wen-zhi; Chen, Jin-Yun; Wang, Zhi-Biao (Frontiers in Surgery, 2021)
Objective: To evaluate factors in predicting the treatment outcome of ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation for uterine fibroids with a non-perfused volume ratio (NPVR) of at least 80%. Methods: One thousand patients with uterine fibroids who received USgHIFU were enrolled. Thirty-two independent variables of 4 dimensions data set, including general information of patients, clinical symptoms, laboratory tests, and fibroid imaging characteristics, were carried out to investigate the potential predictors of the NPVR of at least 80% by multivariate logistic regression. NPVR was the gold standard for evaluating the efficiency of HIFU ablation, and the NPVR of at least 80% as sufficient ablation while partial ablation was with a NPVR of less than 80%. Results: 758 fibroids out of 1000 obtained sufficient ablation and 242 partial ablation, and the median NPVR was 88.3% (interquartile range: 80.3%-94.8%). The probability of NPVR reaching 80%: fibroids with signal intensity of T2WI of hypointense, isointense and hyperintense was 86.4%, 76.5% and 62.6% respectively; fibroids with enhancement type of T1WI of slight, irregular and regular was 81.5%, 73.6% and 63.7%, respectively; Fibroids with utrine anteroposterior of 30 mm to 130 mm was 57.7% to 78.3%, respectively. Patients with platelet count of 50×109 /L to 550×109 /L, the probability of NPVR reaching 80% from 53.4% to 80.1% respectively. Conclusions: The predicting of NPVR≥80%, the signal intensity on T2WI was the most important factor affecting ablative efficiency, followed by enhancement type on T1WI, uterine anteroposterior, and platelet count.